EXPORT MARKETING STRATEGY FOR BALI’S SALAK GULA PASIR FRUIT IN AN EFFORT TO INCREASE SALES IN THE INTERNATIONAL MARKET - Alfon Syaputra; Ni Putu Nina Eka Lestari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to formulate a marketing strategy that can be implemented to increase sales of Balinese sugar palm snake fruit in the international market. The research method used in this study is:The qualitative method used aims to deeply understand the phenomena and perceptions of the Balinese sugar palm fruit industry players so that the results obtained can formulate appropriate marketing strategies according to market situations. The analytical tools in this study use SWOT analysis, IFAS Analysis and EFAS Analysis, as well as Internal Matrix and External Matrix. The selection of respondents in this study was done purposively. Respondents to determine external factors consisted of government agencies, namely customs and plant quarantine agencies and foreign consumers with statements compiled based on the PEST approach (Politics, Economics, Social, and Technology) while respondents to determine internal factors consisted of two snake fruit farmers and employees of the Balinese sugar palm fruit export company with statements compiled based on the concept of the 7 P Marketing Mix (Product, Price, promotion, place, people, promotion, physical evidence). The results of the study show that the position of Balinese sugar palm fruit is in quadrant 1 cell 6 in the internal - external matrix. This position indicates that the right strategy to be carried out is Growth Strategy. In addition, the results of the SWOT analysis in this study produce16 strategies that can be implemented so that efforts to increase sales volume can be achieved optimally.